A comprehensive evaluation for the treatment of lupus nephritis. (March 2017) - Zampeli, Evangelia; Klinman, Dennis M.; Gershwin, M. Eric; Moutsopoulos, Haralampos M.
Abstract: Systemic lupus is the prototypic human autoimmune disease. It is a kaleidoscope of autoreactivities, with clear indications of both a genetic and environmental basis. Indeed, it is a disease that can manifest in virtually every tissue and organ and can also be found spontaneously in a number of animal species, including dogs, cats and horses. Moreover, there are multiple murine models of lupus, the first of which, New Zealand Black (NZB) mice, were discovered in 1959. Despite an enormous effort from scientists in multiple disciplines, the etiology of lupus remains elusive and the introduction of new therapies has been disappointing. Fortunately, significant advances have occurred to help patients through the general principles of internal medicine, including antibiotics, dialysis, and of course use of steroids and immunosuppressive agents. However, the magic bullet has yet to be discovered. One of the major causes of morbidity in lupus remains lupus nephritis and there has been significant effort and encouragement in understanding the pathogenesis, renal histologic classification, and use of therapeutic protocols to induce and sustain remission of lupus nephritis. Indeed, the first use of evidence-based clinical trials in lupus was initiated by Dr. Alfred D. Steinberg at NIH in pioneering studies involving either oral or intravenous pulses of cyclophosphamide, azathioprine or corticosteroids alone and/or some combination. Cyclophosphamide intravenously proved to be superior and the use of cyclophosphamide in combination with methylprednisolone remained the standard protocol for the treatment of lupus nephritis for decades. Although alternative therapies have been introduced, including mycophenolate mofetil, the use of therapies first pioneered at NIH may still be considered standard of care in the appropriate indications. More targeted therapies are much desired. In this review we provide a comprehensive overview of lupus nephritis and the evolution of clinical treatments. Highlights: Since the first groundbreaking evidence-based studies at NIH cyclophosphamide is still used to induce remission in LN. Early recognition (based on clinical/serologic/laboratory parameters and renal biopsy) of lupus nephritis is essential. Lupus nephritis therapeutic goals: achieve rapid remission, avoid renal flares and minimize treatment-associated toxicity.